2016
DOI: 10.12691/ijcd-2-2-3
|View full text |Cite
|
Sign up to set email alerts
|

A Metabonomics Study on Celiac Disease by CART

Abstract: Celiac disease (CD) is an immune reaction as a consequence of ingestion of gluten. Diagnosis of CD is not easily using the clinical tests. Then, the discovery of appropriate methods for CD diagnosis is necessary. This study was concentrated to seek the metabolic biomarkers causes of CD compare to healthy subjects.In the present study, we classify CD and healthy subjects using classification and regression tree (CART). To find metabolites in serum which are helpful for the diagnosis of CD, the metabolic profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Rezaei-Tavirani et al (2012) Serum, NMR Lipids, lactate, and choline were changed in CD patients. Fathi et al (2013a) Serum, NMR Lactate, valin and lipid levels in CD patient are lower than healthy controls Aprea et al (2014) Exhaled breath, PTR-TOF-MS Exhaled breath of patients with CD on GFD was similar to the exhaled breath of healthy people. autoimmune diseases.…”
Section: Referencementioning
confidence: 93%
See 1 more Smart Citation
“…Rezaei-Tavirani et al (2012) Serum, NMR Lipids, lactate, and choline were changed in CD patients. Fathi et al (2013a) Serum, NMR Lactate, valin and lipid levels in CD patient are lower than healthy controls Aprea et al (2014) Exhaled breath, PTR-TOF-MS Exhaled breath of patients with CD on GFD was similar to the exhaled breath of healthy people. autoimmune diseases.…”
Section: Referencementioning
confidence: 93%
“…Early diagnosis and compliance with a gluten-free diet are important for potential coeliac disease patients. Several studies have used NMR and MS methods to identify biomarkers in coeliac disease (Bertini et al, 2009;Bernini et al, 2011;Rezaei-Tavirani et al, 2012;Sellitto et al, 2012;Fathi et al, 2013a;Aprea et al, 2014). Those results showed the following findings: 1) overt CD, potential CD and healthy controls could be distinguished by metabolic profiling; 2) a strict gluten-free diet (GFD) is benefit to disease control; and 3) alterations of gut microbiota were associated with onset of coeliac disease.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Classification and Regression using the method tree (CART) was performed to identify predictors of CD based on metabolic profile. This analysis revealed that the most important predictor of CD was lactat metabolite (with a lower level than 0.1026), so it was revealed a reduction in blood serum level of milk compared to healthy controls [12].…”
Section: Discussionmentioning
confidence: 93%
“…Some of these metabolites are also important in other brain diseases. The changes in metabolites' levels may indicate the disease state (8). In another way, specific kinds of metabolites may be recognized as potential biomarkers for disease determinations (9).…”
Section: Original Articlementioning
confidence: 99%